Analisis Naratif Biografi Hoegeng Iman Santoso sebagai Bahan Ajar Membaca Biografi - Awaliyah, Mia, Drs. Agus Budi Wahyudi, M. Hum (2016)
Mia Awaliyah/ A310120201. NARRATIVE ANALYSIS OF BIOGRAPHY HOEGENG IMAN SANTOSO AS INTRUCTIONAL MATERIALS READING BIOGRAPHY. Essay. Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta. September, 2016. Given the condition of the students who deviated from the norms of good as the nation's future, character education is indispensable. Implementation of character education through learning to read biographies is necessary, taking into account the selection of instructional materials containing biographies of quality and value as well as socio-cultural students in line with the development of learners. This research is qualitative. Data collection techniques were used that refer to the log and documentation techniques. Data analysis techniques used in this study is equivalent methods, agih methods, and read a marker techniques. Then the validity of the data using a triangulation technique theory. The purpose of this study: (1) finding a form of the adjective in four biographies of Hoegeng Iman Santoso, (2) expalin character of Hoegeng Iman Santoso indicated by adjectives in a sentence, (3) implements the analysis of biographical Hoegeng Iman Santoso as one of the teaching materials text of reading biographies. The results of this study as follows, (1) Found type based adjective basic namely, intimate, smart, friendly, neat, seriously, orderly, enthusiastic, dear, humorous, sure, diligent, to be honest, active, capable, and memorized. Then based on the derivative adjective found eight groups: open, sincerely, do not hate, determined, function, sympathetic, and respect. (2) Found 22 characters Hoegeng Iman Santoso, namely: intimate, intelligent, friendly, open, earnest, orderly, serious, orderly, passionate, affectionate, humorous, confident, diligent, honest, active,capable, reminders, not hate, determination, responsible, caring / sympathetic, and appreciative. (3) Then from 22 characters Hoegeng discovered show that Iman Santoso Hoegeng biography can be used as teaching materials to read biographies School (SMA) class XI specialization language. Keywords: narrative, adjectives, characters, Hoegeng Iman Santoso, teaching materials.